2022
DOI: 10.3390/ijms23147832
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Caffeine Interactions in Choline Chloride Natural Deep Eutectic Solvents: Solubility Measurements and COSMO-RS-DARE Interpretation

Abstract: Solubility of active pharmaceutical ingredients is an important aspect of drug processing and formulation. Although caffeine was a subject of many studies aiming to quantify saturated solutions, many applied solvents suffer from not being environmentally friendly. This work fills this gap by presenting the results of solubility measurements in choline chloride natural deep eutectic solvents, ccNADES, comprising one of seven of the following polyalcohols: glycerol, sorbitol, xylitol, glucose, sucrose, maltose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 128 publications
1
9
0
Order By: Relevance
“…However, we note that none of the implementations reproduces exactly the experimentally measured solubilities. Similar observations have been reported by Jeliński et al 100,101 where they compared the calculated caffeine solubilities in neat and binary solvents with the available experimental data and found that the solubility of caffeine in some of these solvents is not well captured. The absence of fusion data poses an additional hurdle in predicting solubilities using COSMO-RS.…”
Section: Solvent Screening and Solubility Predictionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, we note that none of the implementations reproduces exactly the experimentally measured solubilities. Similar observations have been reported by Jeliński et al 100,101 where they compared the calculated caffeine solubilities in neat and binary solvents with the available experimental data and found that the solubility of caffeine in some of these solvents is not well captured. The absence of fusion data poses an additional hurdle in predicting solubilities using COSMO-RS.…”
Section: Solvent Screening and Solubility Predictionsupporting
confidence: 85%
“…Therefore, predicting solubilities in these systems using COSMO-RS becomes challenging and less reliable due to the reliance on fusion data for accurate predictions. 101 Although accurate solubility estimations via COSMO-RS simulation packages are not easily achieved, we can nonetheless use fast and efficient computational screening of solvents to limit candidate solvents for a given API and immediately rule out the solvents with very unfavorable solubility across multiple predictive approaches. The solubility of caffeine in selected solvents ranked by three COSMO-RS implementations is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is an additional interesting aspect worth emphasizing. According to our earlier studies [ 53 , 54 , 55 ], the addition of water to the DES systems may improve the solubility of active pharmaceutical ingredients even more compared to neat eutectic systems. Therefore, the best-performing compositions for both studied DES systems were chosen for further experiments and used in mixtures with water in different proportions.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42] The DES have proven to have the ability to significantly increase the solubility and bioavailability of many active pharmaceutical ingredients. [43][44][45] Also our research group has successfully demonstrated the usefulness of using DES for the dissolution of many active substances, including sulfonamides, 46 curcumin, 47 caffeine, 48 and edaravone. 49 Therefore, it seems natural to apply DES in the case of DAP.…”
Section: Materiał I Metodymentioning
confidence: 99%